How Can the Fibonacci Sequence Be Proved by Induction?

I'll also use the fact that F_{2j} = F_{2j+1} - F_{2j-1}.\sum_{k=2}^{2n} F_k F_{k-1} = \sum_{k=3}^{2n} F_k F_{k-1} = F_3 F_2 + \sum_{k=4}^{2n} F_k F_{k-1} = F_4 F_3 + \sum_{k=5}^{2n} F_k F_{k-1} = ... = F_{2n} F_{2n-1} + \sum_{k=2n+1}^{2
  • #1
williampb
2
0
I've been having a lot of trouble with this proof lately:

Prove that,

F[itex]_{1}[/itex]F[itex]_{2}[/itex]+F[itex]_{2}[/itex]F[itex]_{3}[/itex]+...+F[itex]_{2n}[/itex]F[itex]_{2n+1}[/itex]=F[itex]^{2}_{2n+1}[/itex]-1

Where the subscript denotes which Fibonacci number it is. I'm not sure how to prove this by straight induction so what I did was first prove that,

F[itex]_{2}[/itex]+F[itex]_{4}[/itex]+...+F[itex]_{2n}[/itex]=F[itex]_{2n+1}[/itex]-1

And then used that in the other proof.

For F[itex]_{2}[/itex]+F[itex]_{4}[/itex]+...+F[itex]_{2n}[/itex]=F[itex]_{2n+1}[/itex]-1

First,
For n=1 (base case)

F[itex]_{2(1)}[/itex]=F[itex]_{2}[/itex]=1

Then,

F[itex]_{2(k+1)}[/itex]=F[itex]_{2(k+1)+1}[/itex]-1+F[itex]_{2(k+1)}[/itex]
=(F[itex]_{2k+3}[/itex]+F[itex]_{2k+2}[/itex])-1
=F[itex]_{2k+5}[/itex]-1 = F[itex]_{2(k+2)+1}[/itex]-1

Proving that F[itex]_{2k}[/itex]=F[itex]_{2k+1}[/itex]-1 for all k+1.

Now my question is, would this be a valid method for the proof first stated:

F[itex]_{2n}[/itex]F[itex]_{2n+1}[/itex]=F[itex]^{2}_{2n+1}[/itex]-1
F[itex]_{2(k+1)}[/itex]F[itex]_{2(k+1)+1}[/itex]=F[itex]^{2}_{2(k+1)+1}[/itex]-1

Since,

F[itex]_{2(k+1)}[/itex]=F[itex]_{2(k+1)+1}[/itex]-1

Then the equation becomes:

F[itex]_{2(k+1)+1}[/itex]F[itex]_{2(k+1)+1}[/itex]-1=F[itex]^{2}_{2(k+1)+1}[/itex]-1

Something doesn't sit right with me. I feel like this is incorrect. If it is, any and all help would be appreciated. Thank you.
 
Physics news on Phys.org
  • #2
williampb said:
I'm not sure how to prove this by straight induction
It's quite a cute proof by induction, actually, if you can prove (or already know) that [itex]\sum_{k=1}^n F_k^2 = F_n F_{n+1}[/itex].

Let's assume [itex]F_1 = F_2 = 1[/itex] and [itex]F_{n+2} = F_{n+1} + F_n[/itex] for natural numbers n. Since the recursive relation refers to two lesser naturals, we should proceed with strong induction and two base cases.

Hence, for n = 1 we have:
[tex]\sum_{k=1}^{2} F_k F_{k+1} = F_1 F_2 + F_2 F_3 = 1 + 2 = 3 = 4 - 1 = 2^2 - 1 = F_3^2 - 1 = F_{2(1)+1}^2 - 1.[/tex]
For n = 2 we have:
[tex]\sum_{k=1}^{4} F_k F_{k+1} = 3 + F_3 F_4 + F_4 F_5 = 3 + 6 + 15 = 24 = 25 - 1 = 5^2 - 1 = F_5^2 - 1 = F_{2(2)+1}^2 - 1.[/tex]
Now suppose that [itex]\sum_{k=1}^{2j} F_k F_{k+1} = F_{2j+1}^2 - 1[/itex] for all [itex]j < n[/itex]. We want to show it's true for n itself. Break up the sum into recognizable parts:
[tex]\sum_{k=1}^{2n} F_k F_{k+1} = F_1 F_2 + \sum_{k=2}^{2n} F_k F_{k+1} = 1 + \sum_{k=2}^{2n} F_k (F_k + F_{k-1}) = 1 + \sum_{k=2}^{2n} F_k^2 + \sum_{k=2}^{2n} F_k F_{k-1}.[/tex]
The middle sum is 1 less than the identity at the start of my post. Note that [itex]F_k[/itex] and [itex]F_{k-1}[/itex] commute (luckily!) and so that last sum looks familiar, almost. Write it out in full, cut out a slice to which the induction hypothesis applies, and then deal with the rest.
 

Related to How Can the Fibonacci Sequence Be Proved by Induction?

1. What is the Fibonacci sequence?

The Fibonacci sequence is a mathematical sequence where each number is the sum of the previous two numbers, starting with 0 and 1. The sequence is as follows: 0, 1, 1, 2, 3, 5, 8, 13, 21, 34, etc. It was discovered by Leonardo Fibonacci in the 12th century, and has numerous applications in mathematics and nature.

2. What is a proof by induction?

A proof by induction is a mathematical technique used to prove that a statement or formula holds true for all values of a certain variable. It involves proving the statement is true for a base case, and then showing that if the statement is true for one value, it must also be true for the next value. This process continues until the statement is proven to hold true for all values of the variable.

3. How is Fibonacci proof by induction used?

Fibonacci proof by induction is used to prove various properties or formulas related to the Fibonacci sequence. For example, it can be used to prove that the sum of the first n Fibonacci numbers is equal to the (n+2)th Fibonacci number minus 1. It can also be used to prove identities or patterns within the sequence.

4. What are the steps to a Fibonacci proof by induction?

The steps to a Fibonacci proof by induction are as follows:

  1. Base case: Prove the formula or statement is true for the first value of the variable (usually n=1 or n=2).
  2. Inductive hypothesis: Assume the formula or statement is true for some arbitrary value of the variable (usually n=k).
  3. Inductive step: Using the inductive hypothesis, show that the formula or statement is also true for the next value of the variable (n=k+1).
  4. Conclusion: Conclude that the formula or statement holds true for all values of the variable by the principle of mathematical induction.

5. What are some real-life applications of Fibonacci proof by induction?

Fibonacci proof by induction has applications in various fields such as computer science, economics, and biology. In computer science, it is used to analyze the efficiency of algorithms. In economics, it can be used to model population growth or financial markets. In biology, it can be used to study the growth patterns of certain organisms.

Similar threads

Replies
3
Views
545
  • Linear and Abstract Algebra
Replies
2
Views
1K
  • Mechanical Engineering
Replies
9
Views
1K
  • Calculus and Beyond Homework Help
Replies
20
Views
533
  • Introductory Physics Homework Help
Replies
6
Views
294
Replies
3
Views
895
  • Advanced Physics Homework Help
Replies
10
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
911
  • Precalculus Mathematics Homework Help
Replies
3
Views
1K
  • Special and General Relativity
Replies
28
Views
2K
Back
Top